PENGEMBANGAN DIAGNOSIS TUBERKULOSIS PADA HEWAN KESAYANGAN ANJING MENGGUNAKAN ANTIGEN SPESIFIK Mycobacterium tuberculosisESAT-6 DAN CFP-10 - Tjahajati, Ida; Asmara, Widya; Soebono, Hardyanto (Fakultas Kedokteran Universitas Brawijaya, 2007)
Early diagnosis is one of the important methods to control tuberculosis because this disease is zoonotic which easily spread through the air. Early detection of tuberculosis in dog is also very important since dog as petanimal have a potency to transfer the disease to human or other animals. The discovery of two specific M.tuberculosisantigens, ESAT06 and CFP-10, provide the opportunity to developa specific diagnostic kit for tuberculosis by using ELISA based on the secretion of IFN-γ. The development of a tuberculosis diagnostic kit based on this molecular biology and immunological method would provide a good alternative method to detect tuberculosis specially, accurately as early as possible. The result of this experiment would provide contribution for the development of health science and technology, especially in the eradication of tuberculosis. Keywords: diagnosis, tuberculosis, ESAT-6, CFP-10, interferon-gamma.